Astropharmacy: Roles for the Pharmacist in Space - Shireen Aziz; Muhammad Ahmer Raza; Misbah Noreen; Muhammad Zain Iqbal; Shahid Masood Raza (University of Minnesota Libraries Publishing, 2022)
Since disease is a natural aspect of life, human deep space missions will largely depend on preventing disease, diagnosis, and treatment. Pharmaceuticals are used to identify, treat, prevent, or cure illnesses, but they are unstable on Earth and even more so in space. What if the pharmacist could prepare small quantities of medicines in space, on site, as needed? The alteration in pharmacokinetic and pharmacodynamic (PK-PD) and pharmacogenomics with flying and medications will need to be customised for each person individually and specifically at the point of need because of drug stability issues. We can't meet the expense of bringging everything we might need, so pharmacists must devise ways to manufacture medications in-situ and on-demand. With this skill, pharmacists would be able to fulfill the demand of any exploration mission that involved spaceflight with robust pharmaceuticals that would be stable enough to last the duration of the mission, comprehensive enough to treat all potential medical events, safe, and effective, notwithstanding the known PK-PD and pharmacogenetic alterations that take place during spaceflight. The purpose of this article was to review topics related with Astropharmacy. The topics include: the need of Astropharmacy in space, health-related problems caused by hostile space conditions, storage problems in space, methods to establish the stability and effectiveness of pharmaceutical products in space, and alteration in human physiology including PK-PD and pharmacogenomics and highlight the pharmacist's potential roles in the pharmacies orbiting the space.